PENGARUH AKTIVASI KIMIA ARANG KAYU LABAN TERHADAP EFEKTIVITAS PEMURNIAN BIOGAS & UNJUK KERJA GENERATOR-SET - Azmi Rianur; Abdul Ghofur (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2017)
This study aims to determine the effect of laban charcoal chemical activation on the effectiveness of biogas purification and generator-set performance. This research is conducted by drain biogas from sanitary landfill to biogas purification insulator containing adsorption media in the form of chemical activated charcoal either with NaCl or NaOH liquid, then biogas is stored in the storage tube then flowed to chamber for the reading of CO2 and CH4 using gas analyzer . From this study the following results are obtained: Biogas without purification (CO2 2808.62 ppm and CH4 40.51 ppm), Biogas by purification (CO2 2579,72 ppm, CH4 42,43 ppm and effectiveness equal to 8,1%), at activated NaOH activated medium (CO2 1987,24 ppm, CH4 62,76 ppm and effectiveness 29,2%), NaCl activated adsorption medium (CO2 1920,01 ppm, CH4 75,28 ppm and effectiveness 31,6%) . For the result of generator-set performance test using biogas fuel that has been purified by charcoal of chemical activated charcoal using NaCl that is for no load, got round of 3484,87 rpm, temperature 130,10C, and voltage 240 V (stable), with 350 W load is 2371,2 rpm, temperature is 131,90C, and voltage 150-240 V (not stable), with load of 650 W obtained 2256,5 rpm rotation, temperature 145,70C, and voltage 100-200 V (not stable).